2014
DOI: 10.4143/crt.2014.46.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Cystic Carcinoma of the Breast: A Case Series of Six Patients and Literature Review

Abstract: Adenoid cystic carcinoma (ACC) of the breast is a very rare and indolent tumor with a favorable prognosis, despite its triple-negative status. Due to its rarity, there has been no consensus regarding treatments, and treatment guidelines have not been established. Here, we report on six patients with ACC of the breast. All of the patients initially presented with localized disease and no axillary lymph node metastases. Although some of our patients developed local recurrence or distant metastases, all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…The c-KIT, EGFR expression, and Ki-67 activity is typically low in these cases. 48 Clearly, a large proportion of patients harbor indolent tumors and may survive 5 to 10 years even with little or no therapy, yet others have tumors that grow more rapidly and some have tumors that grow rapidly only after a period of relative stability. A recent analysis of more than 2600 European patients with metastatic ACC confirmed that degree of variability in the clinical course, but overall observed that nearly two thirds of the patients had died after 5 years.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The c-KIT, EGFR expression, and Ki-67 activity is typically low in these cases. 48 Clearly, a large proportion of patients harbor indolent tumors and may survive 5 to 10 years even with little or no therapy, yet others have tumors that grow more rapidly and some have tumors that grow rapidly only after a period of relative stability. A recent analysis of more than 2600 European patients with metastatic ACC confirmed that degree of variability in the clinical course, but overall observed that nearly two thirds of the patients had died after 5 years.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…It is also important to note that although ACC in the breast can seem initially like invasive ductal carcinoma and is typically triple negative (estrogen receptor, progesterone receptor, and HER‐2) it has a generally more favorable prognosis than conventional triple negative breast carcinomas and ACCs arising at other sites. The c‐KIT, EGFR expression, and Ki‐67 activity is typically low in these cases 48. Clearly, a large proportion of patients harbor indolent tumors and may survive 5 to 10 years even with little or no therapy, yet others have tumors that grow more rapidly and some have tumors that grow rapidly only after a period of relative stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ACC of the breast and skin are believed to be less aggressive than similar tumours of the major salivary gland, lung and bronchus [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…When ACC patients have local recurrence or distant metastasis, they still show a sustained and slow progression. Because a longer course of disease increases the risk of recurrence and distant metastasis, the long term follow-up is required (Kim et al, 2014). …”
Section: Prognosismentioning
confidence: 99%